Pucak Giri Raung Temple in Sumberarum Village, Songgon District, Banyuwangi Regency (Study of History, Structure And Temple Functions): Pura Pucak Giri Raung Di Desa Sumberarum, Kecamatan Songgon, Kabupaten Banyuwangi (Studi Tentang Sejarah, Struktur Dan Fungsi Pura) - Saifur Rijal; I kadek Yudiana; I Wayan Mertha; Mahfud (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This research was conducted in Sumberarum Village, Songgon, Banyuwangi which aims to find out; (1) History of Pucak Giri Raung Temple; (2) The structure of the Pucak Giri Raung Temple; (3) The function of the Pucak Giri Raung Temple. This research is historical research, so the steps taken are (1) Heuristic data collection (observation, interviews, study of documents), (2) Criticism of sources, (3) Interpretation and (4) Historiography of historical writing. Based on findings in the field, Pucak Giri Raung Temple was founded in 1972. Its founders, the Hindu community from Jembrana and Karangasem, Bali. At that time, people from Bali moved to Banyuwangi to cultivate cloves. Since then the Hindu community has grown until now. It is called Pucak Giri Raung Temple because the location of the temple is in the hills and under the foot of Mount Raung. The people believe that around the slopes of Mount Raung are the remains of Maharesi Markandeya, the spread of Hindu religious teachings from Java to Bali in the 7th century AD. Pucak Giri Raung Temple is still related to Rsi Markandeya. Because the local people have found relics and a place where Rsi Markandeya meditated. Relics found by local people in the form of sticks. Rsi Markandeya's journey was first to Mount Dieng in Central Java, then continued the journey to Kalibaru sub-district, after that at Gumuk Kancil, Sempu sub-district, continued to Pucak Giri Raung Temple, Sumberasih hamlet, Songgon sub-district, and ended the trip at Besakih Temple in Bali to teach Hinduism. The structure of Pucak Giri Raung Temple uses the Dwi Mandala concept in which this concept divides the temple into two parts, namely Nista Mandala (unholy part) and Utama Mandala (most sacred part). The function of Pucak Giri Raung Temple is divided into three namely, (1) Religious function as a place for prayer and religious ceremonies (2) Religious Education function as a place for pasraman or often called Hindu religious education; and (3) social function as a meeting place for meetings and deliberations